Investment in Bitcoin : A Delusion or Diligence? - Chopra, Monika; Saldi, Rupish (Indian Journal of Finance, 2022)
Bitcoin investment gained great research interest, especially after the onset of the COVID-19 pandemic, a period marked by huge volatility in this asset class. This study investigated Bitcoin’s persistence and hedging properties in the pre-COVID era to establish its efficiency and safety by testing relevant data. We evaluated the role of persistence in Bitcoin trading to highlight its efficiency. The GPH estimator and ARFIMA were used to map the evolving efficiency of the Bitcoin price. Our analysis of intra-day data exhibited the presence of an anti-persistence effect, following the popular conclusion of momentum and speculative trading in the Bitcoin market. The second section of this study evaluated whether Bitcoin played the role of a hedge and an asset of protection in a global portfolio manager’s portfolio during extreme market volatility. Using the Threshold GARCH (TGARCH), we evaluated the trading correlation between Bitcoin prices and four major indices, namely S & P 500, FTSE, Hang Seng, and Nikkei, on daily and weekly data. We identified the time-varying hedge and safety properties of Bitcoin: volatility, speculation, less-traded history, and lack of regulatory infrastructure. Our findings added to the literature by testing the efficiency of Bitcoin in major developed economies using returns of high-frequency data, along with daily returns. We also considered extreme movements in the currency to check its hedging and protection properties in a portfolio of developed market stocks. We recommended that investors be cautious when combining this currency with different stock markets based on our findings.